Efficient Optical-to-THz Conversion Organic Crystals with Simultaneous Electron Withdrawing and Donating Halogen Substituents - Lee, Seung Jun; Kang, Bong Joo; Shin, Myeong Hoon; Lee, Seung Chul; Lee, Seung Heon; Jazbinsek, Mojca; Yun, Hoseop; Kim, Dongwook; Rotermund, Fabian; Kwon, O. Pil (Advanced Optical Materials, 2018)
This study reports on highly efficient nonlinear optical ionic quinolinium crystals with various aromatic anions possessing different spatial volume for controlling the space-filling characteristics and introducing halogen substituents having simultaneous electron-withdrawing and electron-donating effects. The quinolinium crystals with chloro and bromo substituents having simultaneous electron-withdrawing and electron-donating effects on anions exhibit perfect molecular ordering for optimizing the diagonal second-order nonlinear optical response, while the fluoro substituent having relatively small electron-donating effects on anions results in the absence of nonlinear optical response. Compared to widely used 4-methylbenzenesulfonate, the chloro substituent on 4-chlorobenzenesulfonate (CBS) results in decreasing π–π interactions between cations and anions. This leads on the one hand to an enhanced macroscopic nonlinear response and on the other hand to an increased strength of hydrogen bonds between anions, resulting in strong suppression of THz phonon vibration. In THz generation measurements with pump pulses at 1300 nm, 0.39 mm thick 2-(4-hydroxystyryl)-1-methylquinolinium 4-chlorobenzenesulfonate (OHQ-CBS) crystal exhibits excellent optical-to-THz conversion characteristics with 27 times higher peak-to-peak electric field and 3 times broader bandwidth than the well-known 1.0 mm thick inorganic standard ZnTe crystal. In addition, compared to state-of-the-art analogous quinolinium crystals with 4-methylbenzenesulfonate, OHQ-CBS crystal exhibits 1.8 times higher field.
Keywords: Conversion characteristics; Electron-donating effects; Electronwithdrawing; Non-linear optical; Non-linear response; Nonlinear optical response; Organic crystal; Second-order nonlinear optical; electro-optics; nonlinear optics; organic crystals; terahertz waves